2022
DOI: 10.1093/tas/txac067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Bacillus-based direct-fed microbial on in vitro nutrient digestibility of forage and high-starch concentrate substrates

Abstract: Two experiments evaluated the effects of a Bacillus-based direct-fed microbial on in vitro dry matter (DM) and neutral detergent fiber (NDF; Exp. 1), and starch (Exp. 2) digestibility of a variety of ruminant feedstuffs. In Exp. 1, ten forage sources were evaluated: ryegrass, alfalfa hay, leucaena, corn silage, spinifex, buffel grass, flinders grass, Mitchell grass, rhodes grass hay, and Queensland bluegrass. Experimental treatments were a Control, forages with no probiotic inoculation; CON) or forages sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
4
27
2
Order By: Relevance
“…Following experiment 1., data from this and our previous in vitro research study ( Pan et al, 2022 ) were compiled into a larger dataset ( N = 16 forage-based feedstuffs) to understand how Bacillus -based DFM would impact in vitro nutrient digestibility (IVDMD and IVNDFD). Of note, Pan et al (2022) evaluated 10 different single forage-based feedstuffs inoculated or not with the same Bacillus -based DFM (BOVACILLUS; Chr. Hansen A/S) evaluated herein.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following experiment 1., data from this and our previous in vitro research study ( Pan et al, 2022 ) were compiled into a larger dataset ( N = 16 forage-based feedstuffs) to understand how Bacillus -based DFM would impact in vitro nutrient digestibility (IVDMD and IVNDFD). Of note, Pan et al (2022) evaluated 10 different single forage-based feedstuffs inoculated or not with the same Bacillus -based DFM (BOVACILLUS; Chr. Hansen A/S) evaluated herein.…”
Section: Methodsmentioning
confidence: 99%
“…have been recognized ( www.lpsn.dsmz.de ). Recently, Pan et al (2022) reported that a mixture of B. licheniformis and B. subtilis improved in vitro dry matter ( DM ), neutral detergent fiber ( NDF ), and starch digestibility of forage-based and concentrate feedstuffs originated from Australia, indicating that the ability of Bacillus spp. to produce and release a wide type and quantity of enzymes might promote feedstuff or nutrient utilization ( Schallmey et al, 2004 ; Elshaghabee et al, 2017 ; Luise et al, 2022 ) in ruminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Bacillus spp. on in vitro digestibility of forages included in ruminant diets and its ability to increase in NDFd is not novel (Sun et al, 2013; Romero et al, 2015; Jia et al, 2022; Pan et al, 2022). The novelty of our work was the demonstration that the cellulases and xylanases secreted by this microorganism are effectively involved in the recovery of nutrients from fibrous material.…”
Section: Discussionmentioning
confidence: 99%
“…The biological treatment of rice straw resulted in a decrease in ADF concentration and NDF, so it is more easily digested by livestock and has a higher nutritional value. As described in the study of Pan et al [ 30 ], who reported that various forages were inoculated with microbial mixtures containing Bacillus licheniformis and B. subtilis (3.2 × 10 9 CFU/gm DFM), increasing the average digestibility of the DM and NDF with various quality levels of protein and NDF. The increased digestibility of the fiber fraction is due to the cellulase enzymes secreted by microbial inoculants.…”
Section: In Vitro Nutrient Digestibilitymentioning
confidence: 99%